ASTROCYTOMA OF THE BRAIN AND OPHTALMOLOGICAL SIGNS - Yurievna, Safonenko Alexandra; Eduardovna, Ioyleva Elena (MNJ (Malang Neurology Journal), 2020)
Background: The central nervous system neoplasms frequency is 1 per 1700 children aged from 0 up to 15 years old. The problem of the early diagnostics has not been solved yet. The recognition of the pathology, especially in childhood and adolescence is considerably difficult and affects the patient’s life prediction and quality.Objective: To reveal the value of ophthalmological signs in the diagnosis of astrocytoma of the brain.Methods: The young man with the only complaint of the binocular horizontal diplopia during the last year. One month prior to the visit, the patient lost his consciousness. Standard ophthalmic examination, optical coherence tomography (Cirrus HD-OCT), computer perimetry (Humphrey), MRI of the head on (Siemens symphony) with contrast were carried out.Results: Visual acuities were 20/20 for both eyes, an outward motions limitation of both eyes, the presence of paracentral and peripheral scotomas in computer perimetry, the reduction of the visual evoked potentials, pallor of the optic disk, thinning of the nerve fiber layer and ganglion cell on OCT. MRI with contrast revealed the existence of large tumor with a with clear, hilly contours compressing the brain stem. After confirming the presence of a large tumor size, signs of development of occlusal internal and external hydrocephalus, compression of brain stem with the development of life-threatening condition, the patient was referred for neurosurgical consultation. According to the urgent indications the surgical resection of the intracerebral tumor was performed. Biopsy result: pilocytic astrocytoma of the fourth ventricle region.Conclusion: Thus, in the absence of specific cerebral and focal neurological symptoms, the appearance of oculomotor disorders, defects in field of vision and fundus changes can be decisive factors in establishing an accurate diagnosis and timely referral of the patient to a neurosurgeon.